2015
DOI: 10.1289/ehp.1409223
|View full text |Cite
|
Sign up to set email alerts
|

High Ambient Temperatures and Risk of Motor Vehicle Crashes in Catalonia, Spain (2000–2011): A Time-Series Analysis

Abstract: BackgroundExperimental studies have shown a decrease in driving performance at high temperatures. The epidemiological evidence for the relationship between heat and motor vehicle crashes is not consistent.ObjectivesWe estimated the impact of high ambient temperatures on the daily number of motor vehicle crashes and, in particular, on crashes involving driver performance factors (namely distractions, driver error, fatigue, or sleepiness).MethodsWe performed a time-series analysis linking daily counts of motor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 35 publications
8
61
2
Order By: Relevance
“…The findings of this study revealed that an increase in the average temperature caused a statistically significant increase in the rate of RTAs, and ICAs were more frequent than OCAs. This result is supported by studies conducted by Yannis and Karlaftis [67], Basagana et al [63], Al-Harbi et al [66], Wåhlberg [68], Brijs et al [69], Stipdonk [70], Hermans et al [57]. A potential explanation for this result is related to the physiological or psychological effects of high temperatures on drivers, such as altered emotions, increased irritability, reaction time, and fatigue, and decreased concentration, all of which would have detrimental effects on drivers' performance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings of this study revealed that an increase in the average temperature caused a statistically significant increase in the rate of RTAs, and ICAs were more frequent than OCAs. This result is supported by studies conducted by Yannis and Karlaftis [67], Basagana et al [63], Al-Harbi et al [66], Wåhlberg [68], Brijs et al [69], Stipdonk [70], Hermans et al [57]. A potential explanation for this result is related to the physiological or psychological effects of high temperatures on drivers, such as altered emotions, increased irritability, reaction time, and fatigue, and decreased concentration, all of which would have detrimental effects on drivers' performance.…”
Section: Discussionsupporting
confidence: 85%
“…According to several researchers, temperature plays a strong role in road accidents, but there is no common definable relationship between temperature and RTAs [62][63][64]. Some studies have reported that low temperatures are associated with more accidents [65,66]; on the other hand, the majority of the studies have reported that high temperatures are the root cause of road accidents, and more time of sunlight leads to more crashes.…”
Section: Road Traffic Accidents and Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Basagana et al (2015) reported an increased risk of motor vehicle accidents during heat waves. Some recent studies support the inclusion of non-fatal injuries to quantify the total effect of heat exposure on health (Basagana 2014; Otte im Kampe et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many EHE definitions are available from the literature (Anderson and Bell 2011; Basagaña et al 2015; CDC 2013; Easterling et al 2000; Hajat et al 2006; Hajat et al 2010; Huth et al 2000; Kent et al 2014; Kovats and Hajat 2008; Meehl and Tebaldi 2004; Nairn and Fawcett 2014; Pascal et al 2006; Pascal et al 2013; Peng et al 2011; Robinson 2001; Smith et al 2013). Typical EHE definitions can be decomposed into the following core variables:

daily heat metric—heat metrics, such as daily maximum and mean temperature, and diurnal temperature difference are typically employed in EHE definitions;

duration—the number of consecutive days of extreme heat needed to constitute an EHE; the minimum duration for most definitions varies from 2 to 4 days;

threshold type—absolute, which is based on a daily heat metric threshold that does not change, or relative, which is based on an exceedance above a set percentile, which varies according to the underlying daily heat metric distribution for a given location; and

threshold intensity, which indicates the extremity of deviation considered to represent exposure to extreme heat.

…”
mentioning
confidence: 99%